Structure and function of bacterial ion channels - Zubcevic, L (2012)
KirBac channels are prokaryotic homologs of eukaryotic inwardly-rectifying potassium channels, which have served as models for gaining insight into the structure of eukaryotic channels. This thesis focuses on the structure-function relationship in these channels. The first part of this study concerns a novel KirBac channel, KirBac9.2, which contains a unique amino acid sequence in the place of the canonical GYG selectivity filter. Although expressed and purified in a stable and functional form, the protein did not form well-diffracting crystals. Functional studies suggest that KirBac9.2 is non-selective for monovalent cations and a random mutagenesis screen identified a number of activatory mutants in the cytoplasmic domains of the channel. A full electrophysiological investigation of KirBac9.2 channel function is beyond the scope of this study. However, initial studies suggest that it is possible to record currents from KirBac9.2 channels reconstituted into lipid bilayers. The second part of this thesis investigates KirBac3.1, which is a classical KirBac channel containing the consensus GYG sequence for potassium selectivity. Five high resolution structures of a mutant channel are reported, which suggest a new feature in the gating mechanism of KirBac3.1 where a rotation of the cytoplasmic domains is linked to a change in the electrostatic environment of the cytoplasmic cavity. In addition, a functional study of the KirBac3.1 showed that the channel is highly pH sensitive.